Macroeconomic and bank-specific determinants of bank loans to private sector: The case of North Macedonia - Lazarov, Darko; Nikolov, Misho; Simeonoski, Kiril (Industrija, 2023)
The main objective of the paper is to investigate the main determinants of bank credit activity to private sector in North Macedonia. The growth theory and empirical studies show that bank credit activity is one of the most important factors for economic growth, especially in countries where the financial system is dominated by banks. Access to finance for the private sector is crucial for supporting investment, while credit to households has a positive effect on supporting final consumption. However, we focus only on bank credit to the private sector because it has a more significant impact on economic growth through investment in physical capital and technology. To this end, for the period from the fourth quartile of 2007 to the third quartile of 2019, we apply a so-called single-country regression analysis based on the ADRL model. The results show that deposits and bank efficiency have the most significant impact on private bank credit, while nonperforming loans negatively affect private bank credit growth.